Effectiveness of a novel training model for gastric endoscopic submucosal dissection training: a prospective observational study conducted at a single center in Japan - Takahito Toba; Tsuyoshi Ishii; Nobuyuki Sato; Akira Nogami; Aya Hojo; Ryo Shimizu; Ai Fujimoto; Takahisa Matsuda (Clinical Endoscopy)
Background/Aims The efficacy of endoscopic submucosal dissection (ESD) for early-stage gastric cancer is well established. However, its acquisition is challenging owing to its complexity. In Japan, G-Master is a novel ex vivo gastric ESD training model. The effectiveness of training using G-Master is unknown. This study evaluated the efficacy of gastric ESD training using the G-Master to evaluate trainees’ learning curves and performance. Methods Four trainees completed 30 ESD training sessions using the G-Master, and procedure time, resection area, resection completion, en-bloc resection requirement, and perforation occurrence were measured. Resection speed was the primary endpoint, and learning curves were evaluated using the cumulative sum (CUSUM) method. Results All trainees completed the resection and en-bloc resection of the lesion without any intraoperative perforations. The learning curves covered three phases: initial growth, plateau, and late growth. The transition from phase 1 to phase 2 required a median of 10 sessions. Each trainee completed 30 training sessions in approximately 4 months. Conclusions Gastric ESD training using the G-Master is a simple, fast, and effective method for pre-ESD training in clinical practice. It is recommended that at least 10 training sessions be conducted.